Effects of two proprioceptive neuromuscular facilitation techniques in different planes on hamstrings muscles of healthy subjects - Silva, Sidney B.; de Faria, Emerson M.; Almeida, Jamile B.; Bernardes, Ricardo C.; Valenti, Vitor E. [UNESP]; Vanderlei, Luiz Carlos M. [UNESP]; de Abreu, Luiz Carlos (Drunpp-sarajevo, 2012)
Introduction: The proprioceptive neuromuscular facilitation technique (PNF) has been proven to be efficient, since it was found higher gain of joint range-of-motion compared to the classic stretching. This study aimed to perform a comparison between the muscular stretching techniques and the PNF hold-relax on the internal and external sagittal/diagonal plane.Method: Randomly divided in 3 groups by a drawing, 30 healthy male individuals have undergone the test. In group I the hold-relax technique was utilized on the sagittal plane, grupo II receveid hold-relax on the internal and external diagonals, and group III, on which an evaluation was performed, worked as control. All the groups went through tests on the first, fifth and fifteenth day after the application of the different approaches. In this evaluation it was used a Flexis (R) Fleximeter.Result: Group II (diagonal) obtained statistically significant gain of 13.99% in the immediate post-test and post test later obtained a loss of 4.81%, group I (sagittal) showed no statistical difference as the group III (control).Conclusion: We conclude that the technique of PNF in the diagonal plane is effective in the flexibility of the hamstring muscles.
Keywords: Stretching; Muscle Stretching Exercises; Muscles; Lower Extremity